Cochlear Implantation of Bilaterally Deafened Patients with Tinnitus Induces Sustained Decrease of Tinnitus-Related Distress - Knopke, Steffen; Szczepek, Agnieszka J.; Häussler, Sophia Marie; Gräbel, Stefan; Olze, Heidi (Frontiers in Neurology, 2017)
Objective: Tinnitus is a common symptom of hearing impairment. Patients who are bilaterally hard of hearing are often affected by tinnitus. However, they cannot undergo any of the standard tinnitus therapies, since they rely on hearing. Cochlear implantation (CI) used to treat severe hearing disabilities such as bilateral hearing loss, was also shown to reduce tinnitus. Our goal was to determine if CI induces sustained reduction of tinnitus. We performed prospective, longitudinal analyses of tinnitus-related distress in a uniform group of bilaterally deafened patients after cochlear implantation. Methods: The homogenous sample consisted of forty-one patients who met the inclusion criteria and were consecutively included in this study. The impact of unilateral CI on tinnitus-related distress, health-related quality of life and hearing abilities was studied with validated instruments. The follow-up appointments were scheduled at 6, 12 and 24 months after CI surgery. During the appointments, hearing abilities were estimated with monosyllabic Freiburg test whereas the tinnitus-related distress, the health-related quality of life and the subjective hearing were measured with standard questionnaires (tinnitus questionnaire TQ, Nijmegen Cochlear Implantation Questionnaire NCIQ and Oldenburg Inventory OI, respectively). Results: Tinnitus-related distress decreased significantly from the mean TQ score of 35.0 (SD = 19.6) prior to surgery, to the mean TQ = 27.54 (SD = 20.0) six months after surgery and remained sustained low until the end of follow-up period. In addition, cochlear implantation significantly improved the hearing abilities and the health-related quality of life of all patients. Conclusions: The results from our prospective study suggest that in a homogenous sample of bilaterally deafened, implanted patients who report having tinnitus prior to surgery, cochlear implantation alone not only improves the hearing abilities but also significantly reduces the tinnitus-related distress and improves the health-related quality of life in a sustained way.